Perceived Socio-Economic, Psychological and Academic Effects of Gold Mining in the Lives of Learners in Panique National High School - Legaspi, Raizel May (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the perceived socio-economic, psychological, and academic effects of gold mining on learners of Panique National High School in Aroroy, Masbate. Guided by the System Theory, Symbolic Interactionism, and Conflict Theory, the study employed descriptive-comparative and descriptive-correlational research designs to examine differences and relationships among the study variables. A survey questionnaire using a five-point Likert scale was administered to 293 randomly selected learners from a population of 1,101 through stratified random sampling based on Slovin's Formula. Data were analyzed using frequency count, percentage, weighted mean, Pearson Product-Moment Correlation Coefficient, and the independent samples t-test. The findings revealed that learners perceived gold mining to have a very high socio-economic effect, an extremely high psychological effect, and a very high academic effect. No significant differences were found between male and female respondents regarding the socio-economic and psychological effects, whereas a significant difference was observed in the perceived academic effects. Significant positive relationships were identified between respondents' age, grade level, and years of residency and their perceived socio-economic, psychological, and academic effects of gold mining. Respondents strongly supported interventions emphasizing learner welfare, environmental protection, educational continuity, and community development. The study concludes that gold mining substantially influences learners' socio-economic conditions, psychological well-being, and academic experiences and recommends collaborative interventions among local government units, mining companies, educational institutions, and other stakeholders, as well as further studies involving a broader population of learners. The study aligns with Sustainable Development Goal (SDG) 3: Good Health and Well-Being, SDG 4: Quality Education, SDG 8: Decent Work and Economic Growth, SDG 12: Responsible Consumption and Production, and SDG 16: Peace, Justice, and Strong Institutions by promoting learner well-being, responsible mining practices, quality education, and effective governance. Its findings contribute to educational, public health, environmental, socio-economic, and policy sustainability by providing evidence that can support informed decision-making and sustainable interventions in mining-affected communities.
Keywords: Academic Performance; Gold Mining; Learners; Psychological Effects; Socio-Economic Effects; Sustainable Development; Panique National High School